2021
DOI: 10.1007/s41465-021-00212-9
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality as a Non-Pharmacological Adjunct to Reduce the Use of Analgesics in Hospitals

Abstract: Virtual reality (VR) has become an increasingly viable non-pharmacological adjunct to reduce the use of analgesics in hospitals. Within the context of the ongoing opioid epidemic, VR can serve as an invaluable alternative to traditional pain management techniques. While VR research continues to advance, there is no clear consensus on the terms used to describe critical aspects of VR. This paper presents how immersion, presence, and agency encapsulate the VR experience and investigates the methods by which VR c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
0
17
0
3
Order By: Relevance
“…Increased levels of anxiety can lead to worsening pain perception, decreased pain threshold and less cooperative patients [ 20 , 48 ]. We found significantly higher levels of anxiety in women, and such gender differences have been reported elsewhere [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased levels of anxiety can lead to worsening pain perception, decreased pain threshold and less cooperative patients [ 20 , 48 ]. We found significantly higher levels of anxiety in women, and such gender differences have been reported elsewhere [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Strong evidence has also shown that the quality of VR and the amount of immersion as well as interactivity delivered by the VR technology directly correlates with the measured quantity of analgesic effect [ 8 , 9 , 48 ]. Even though the sense of presence and immersion measured according to Slater in our patients was medium (probably due to interruptions, and the busy setting ED), our simulation still proved to be effective and safe with good subjective user satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the use of HMDs has emerged in other relevant fields, such as social learning spaces-e.g., classrooms or museums; Scavarelli et al 2021-and other industrial applications such as architecture, engineering, and construction (Alizadehsalehi et al , 2020Alizadehsalehi and Yitmen 2021). Important clinical applications of immersive VR HMDs include the provision of VR therapy for the non-pharmacological treatment of pain (Pourmand et al 2018;Theingi et al 2021), and the treatment of mental disorders in a safe and controllable setting-e.g., eating disorders (Matamala-Gomez et al 2021), anxiety disorders such as phobias (Boeldt et al 2019), and post-traumatic stress disorders (Oing and Prescott 2018). HMDs have also been successfully employed to reduce patients' cognitive decline (Gerber et al 2019;Sokolov et al 2020).…”
Section: General Applications Of Hmdsmentioning
confidence: 99%
“…It will incorporate an increasing number of breakthroughs, and facilitate the interventions carried out by health professionals who provide care to children to treat painful injuries, such as burns. One of its main bene ts is undoubtedly the fact that it can be adapted to any treatment, not just for certain clinical conditions, but for patients' speci c, individual needs (Theingi et al, 2021).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%